IMPLEMENTING COMMUNICATIVE LEARNING STRATEGIES IN ENGLISH LANGUAGE TEACHING FOR SENIOR HIGH SCHOOL STUDENTS: A REFLECTIVE STUDY DURING TEACHING PRACTICE - Salviya, Nafsiatul; Zainuddin, Zainuddin (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2025)
This reflective study explores the implementation of communicative learning strategies in teaching English at a senior high school during a one-month teaching practice in an Islamic boarding school setting. The aim is to analyse how communicative approaches such as role-play, group discussion, and real-life interaction tasks can be effectively applied without reliance on digital tools. Using a qualitative descriptive method, data were collected through classroom observation, reflective journals, teaching documentation, and student interviews. The findings indicate that communicative strategies significantly improved students' engagement and speaking confidence, despite limited technological support. Interview responses revealed that students felt more motivated and involved when participating in real-life based communication activities rather than rote learning. Observational and documentation data further confirmed that learner-centered methods encouraged greater autonomy and peer collaboration. The study also reveals several challenges, including time constraints and students’ varying language proficiency levels, which at times hindered balanced participation. However, adaptive teaching techniques such as differentiated instructions, visual aids, and role-based tasks proved effective in addressing these issues. This study contributes practical insights into English language teaching in resource-limited contexts and highlights the importance of contextual flexibility. Furthermore, it emphasizes the value of reflective teaching practices for pre-service teachers, particularly in environments where modern technological tools are limited or unavailable. Ultimately, the findings advocate for the integration of communicative learning strategies to enhance learner motivation and speaking fluency in traditional educational settings.